Epidemiology of cryptosporidiosis in dairy calves in central and eastern Algeria - DADDA, A; MOHAMED-CHERIF, A; AIT-OUDHIA, KH; AOUN, L; KHELEF, D (Journal of the Hellenic Veterinary Medical Society, 2022)
The purpose of our survey is to estimate the frequency of Cryptosporidium spp in dairy calves under 60 days of age, the pathogenic role of Cryptosporidium spp in the development of diarrhea, the intervention and association of other enteropathogens often involved in neonatal diarrhea and the possible relationship between infection and certain farming practices in order to estimate the share of risk factors, and on the other hand, to compare between the modified Ziehl-Neelsen staining method and the copro-ELISA test. We found 35 positive samples out of 223 faecal samples analyzed by modified Ziehl-Nielson staining, with a prevalence of 15.69%, the infected calves had 4 times the risk of diarrhea (RR= 4), the age group [8-15 days] is the most susceptible to infection compared to the other age groups (31.1%; p<0.05). The ELISA test revealed that 33 out of 92 calves were infected by Cryptosporidium spp., with a prevalence of 35.87%, showing a sensitivity and specificity of Ziehl-Neelsen staining of 51.5% and 96% respectively.